Transcriptome analysis reveals differential effects of beta-cypermethrin and fipronil insecticides on detoxification mechanisms in Solenopsis invicta - Siddiqui, Junaid Ali; Luo, Yuanyuan; Sheikh, Umer Ayyaz Aslam; Bamisile, Bamisope Steve; Khan, Muhammad Musa; Imran, Muhammad; Hafeez, Muhammad; Ghani, Muhammad Imran; Lei, Nie; Xu, Yijuan (Frontiers in Physiology, 2022)
Insecticide resistance raised many challenges for insect pest control, particularly destructive pests such as red imported fire ant (Solenopsis invicta). In recent years, beta-cypermethrin and fipronil have been extensively used to manage invasive ants, but their effect on resistance development in S. invicta is still unknown. To investigate the resistance development, the populations of S. invicta were collected from 5 different cities in Guangdong, China. Results showed a 105.71 and 2.98 folds increase in resistance in the GZ population against fipronil and beta-cypermethrin, respectively. The enzymatic activities of the Acetylcholinesterase, Carboxylases, and Glutathione S-transferases were significantly increased with increasing beta-cypermethrin and fipronil concentrations. In transcriptomic analysis, 117 differentially expressed genes (DEGs) were identified in BC-ck vs BC-30 treatments (showing 39 up-regulated and 78 down-regulated), 109 DEGs in F-ck vs F-30 (33 up-regulated and 76 down-regulated), and 499 DEGs in BC-30 vs F-30 (312 upregulated and 187 downregulated). The Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that DEGs associated with insecticide resistance were significantly enriched in Metabolic pathways, AMPK signaling pathway, insulin signaling pathway, carbon metabolism, and Peroxisome, fatty acid metabolism, drug metabolism enzyme and metabolism of xenobiotics by cytochrome P45. Furthermore, we found that DEGs important for insecticide detoxification pathways were differentially regulated under both insecticide treatments in S. invicta. Furthermore, we found that DEGs important for insecticide detoxification pathways were differentially regulated under both insecticide treatments in S. invicta. The comprehensive transcriptomic data confirmed that detoxification enzymes play a significant role in insecticide detoxification and the resistance development in the S. invicta in Guangdong province. Numerous pesticide-related genes, GO terms, and KEGG pathways were identified, showing S. invicta workers resistance to both insecticides. Importantly, this transcriptome profile variance serves as a starting point for future research into the insecticide risk evaluation and molecular mechanism of insecticide detoxification in invasive red imported fire ants.